AS MUITAS FACES DE MACHADO: A CONSTRUÇÃO DO ETHOS RETÓRICO EM CONTOS MACHADIANOS THE MANY FACES OF MACHADO: THE CONSTRUCTION OF THE RHETORICAL ETHOS IN MACHADO’S TALES - Alves, Andreia Carla Melegati Rodrigues; Figueiredo, Maria Flávia (Revista do SELL, 2016)
RESUMO: Neste trabalho, teremos, como arcabouço teórico, estudos advindos do âmbito da linguística, mais especificamente das áreas da Retórica e da Argumentação. A partir dessas áreas, contaremos com os conceitos de éthos, de figuras de presença e repetição, e com os de figuras de retórica, como a metáfora e a prosopopeia. A análise, que tem como corpus o conto “A cartomante”, do escritor Machado de Assis, objetiva averiguar a constituição do éthos do contista no corpus selecionado. Ademais, busca observar também as estratégias argumentativas utilizadas pelo orador, com vistas à adesão do auditório/leitor. Para tanto, efetuamos uma análise qualitativa do conto, a fim de apreender os ethé evidenciados. Com essa análise, esperamos contribuir com a ampliação do estudo em torno da constituição do éthos retórico no conto “A cartomante”. PALAVRAS-CHAVE: retórica; éthos; conto; Machado de Assis. ABSTRACT: In this work, we have, as a theoretical framework, studies from the scope of linguistics, specifically in the areas of Rhetoric and Argumentation. From these areas, we will have the concepts of ethos, of presence and repetition figures, and of the rhetorical figures such as metaphor and personification. The analysis, whose corpus is the tale “The fortune teller”, from the writer Machado de Assis, aims to investigate the constitution of the ethos of the storyteller in the selected corpus. In addition, it also seeks to observe the argumentative strategies used by the speaker, in order to get the auditorium’s/reader’s adhesion. Therefore, we made a qualitative analysis of the tale, to grasp the evidenced ethe. With this analysis, we hope to contribute to the expansion of the study about the constitution of rhetorical ethos in the tale “The fortune teller”. KEYWORDS: rhetoric; ethos; tale; Machado de Assis.